Method of Continuous Variations: Applications of Job Plots to the Study of Molecular Associations in Organometallic Chemistry. Issue 46 (24th October 2013) - Renny, Joseph S.; Tomasevich, Laura L.; Tallmadge, Evan H.; Collum, David B.
Abstract Applications of the method of continuous variations (MCV or the Method of Job) to problems of interest to organometallic chemists are described. MCV provides qualitative and quantitative insights into the stoichiometries underlying association of m molecules of A and n molecules of B to form AmBn . Applications to complex ensembles probe associations that form metal clusters and aggregates. Job plots in which reaction rates are monitored provide relative stoichiometries in rate‐limiting transition structures. In a specialized variant, ligand‐ or solvent‐dependent reaction rates are dissected into contributions in both the ground states and transition states, which affords insights into the full reaction coordinate from a single Job plot. Gaps in the literature are identified and critiqued.